Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae) - Khaefi, Roozbehan; Esmaeili, Hamid Reza; Sayyadzadeh, Golnaz; Geiger, Matthias F.; Freyhof, Jörg (Zootaxa, 2016)
Squalius namak, new species, from the endorheic Lake Namak and Kavir basins in Iran, is distinguished from the species of the genus Squalius in the Persian Gulf and the southern Caspian Sea basins by having a wide and thick symphysial knob on the lower jaw, a convex posterior anal-fin margin, a bold, dark-grey or brown, roundish or crescent-shaped blotch at the posterior tip of each flank scale and orange caudal-, anal- and pelvic-fin rays in life. Squalius namak is also characterized by four fixed, diagnostic nucleotide substitutions in the mtDNA COI barcode region.